Considerações sobre o ensino da música no Brasil - Carrasqueira, Antonio Carlos Moraes Dias (Estudos Avançados, 2018)
This article is about the teaching of the flute and others melodic instruments – namely winds and strings. It argues that music education in Brazil must address more deeply certain important aspects to empower musicians to have creative mastery of their instrument in a dialogue with their cultural heritage. The author proposes a methodology that seeks not only technical development on an instrument, but also the complete understanding of the musical language and the development of harmonic awareness. With this aim, he proposes a manner of practicing based on creativity, improvisation and composition, instead of the mere repetition of established patterns.